Analysis of Accident and Occupational Diseases with HAZOP Method and The Risk Control of Batik Papringan Workers, Banyumas - Parmasari, Damairia Hayu; Suryanto, Suryanto (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
An industry that has danger is Batik Papringan, Banyumas. Workers have not implemented Occupational Safety and Health (OSH) at work. It can be seen from the physical environment with poor lighting, workplaces that do not apply Ringkas, Rapi, Resik, Rawat, Rajin (5R), not using Personal Protective Equipment, unergonomic position, and feeling anxious due to decreased demand. Therefore, it is necessary to analyze occupational accidents and diseases and their control. The study took time in August 2020. The population was 200 people. The sample was obtained with the inclusion criteria, namely all Batik workers who were actively working until August 2020, while the exclusion criteria were workers who changed professions so that 190 people were obtained. The research design was cross-sectional with mixed-method analysis. The research was conducted using the HAZOP (Hazards and Operability Studies) sheet instrument. HAZOP sheet consists of job observation, hazard identification, Likelihood, and Consequences scoring, risk categorization, and control. The calculation results show that there is an extreme risk of three hazards (exposure to chemicals from wax, cloth dye, wood dust; bending attitude, static position; not applying 5R). The three extreme risks are respiratory disorders, dermatitis, fatigue, low back pain, Carpal Tunnel Syndrome (CTS), effectiveness, and efficiency of work decrease. The conclusion is that workers are at extreme risk. Employees need to be committed to risk management through disciplined risk control.